The OEIS complex - clinical & radiological evaluation - HK Dutta; Dhaval D Dhingani; RK Gogoi; Deb K Boruah (Archive of Urological Research - Peertechz Publications, 2021)
The OEIS complex comprises a constellation of complex and severe malformations of the abdominal wall, gastrointestinal and genitourinary tracts, and spinal cord. The malformation results from improper closure of the ventral abdominal wall due to failure of convergence of cephalo-caudal and lateral folding of the embryo during early gestation. The rarity of the condition suggests etiologic heterogeneity and the possible role of environmental and genetic factors. We present clinical and imaging findings of the OEIS complex in a neonate.